Dīwān-i Jāmī. Volume 2 : Wāsiṭat al-ʿaqd, khātimat al-ḥayāh - Jāmī, ʿAbd al-Raḥmān, (Miras Maktoob, ISBN: 9789004365452., 2019)
Regarded by many as the last great mystical poet of medieval Persia, ʿAbd al-Raḥmān Jāmī (d. 898/1492) spent the greater part of his life in Herat. As a student, he excelled in every subject he engaged in and appeared destined for an academic career. But then, in his early thirties, he went through a spiritual crisis that ended in him joining the Herat branch of the mystical Naqshbandiyya order, led by the charismatic Saʿd al-Dīn Kāshgharī (d. 860/1456). A protégé of three successive Timurid rulers in Herat, Jāmī's wide network of friendships and relations extended from spiritual and literary circles through the political to the academic. With 39.000 lines of verse and over 30 prose works to his name, Jāmī's literary production is quite overwhelming. His Dīwān , published here in two volumes, underwent various changes before he finalized it in 896/1491. This best edition so far is based on some of the oldest surviving manuscripts. 2 vols; volume 2.